Cerebral Radiation Necrosis in Pediatric Patients. (1st February 2015) - Plimpton, S. Reed; Stence, Nicholas; Hemenway, Molly; Hankinson, Todd C.; Foreman, Nicholas; Liu, Arthur K.
Abstract : Radiation necrosis is a well-described toxicity following radiation therapy in the brain. There is little data regarding the incidence of radiation necrosis in pediatric patients. We retrospectively reviewed our experience with 101 children with solid brain tumors. Radiation necrosis was diagnosed by examination of magnetic resonance imaging. Median follow-up for all patients was 13 months (range 3–51). Radiation necrosis occurred in 5% (5/101) of cases with a median time to onset of 1.2 months. In three of these children, the child was symptomatic, requiring management with steroids and bevacizumab. Radiation necrosis did not correlate with the administration of chemotherapy, age at treatment, or planning treatment volume. Our experience with pediatric patients treated with radiotherapy for solid brain tumor suggests that children may have an increased likelihood to develop radiation necrosis compared to adults.